Thus ‘the Writer’s Wife’ Writes? A Critical Conversation on Pragati Rai’s Bildungsroman - Shrestha, Tara Lal; Shrestha, Bidhya (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This research explores Pragati Rai’s life history from a naïve village girl to becoming an assertive author. It examines how her life stories intersect gender issues with politico-cultural contexts revealing resistance consciousness that counter deep-rooted hegemonic social order. Her husband Rajan Mukarung, a well-established Nepali writer, supports her bildungsroman. However, she revolts to the end embracing independence through an unofficial separation from her husband. Alike her female protagonists of the novel Lekhaka ki Swasni (The Author’s Wife) and Thangra (The Stake) and the poetic persona of her collection of poems Baadee Bigyapti (Statement of the Badi Women), she appears seeking the subaltern publics of her own to actualize her voice. As theoretical notions of Gayatri Chakravorty Spivak, Naila Kabeer, and Nancy Frazer propose alternative public spheres for the existence of the subaltern women, the critical conversation on rebellious writer Pragati Rai’s bildungsroman story demands deeper level of discourses on the position of women in Nepali literary context.